The role and possibilities of psychodiagnostic methods in the formation of socioemotional intelligence in adolescents - Tulyaganova Robiyabonu (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
In this article, psychological conditions related to the psyche of adolescents, their stabilization through psychodiagnostic methods and improvement of mental health of adolescents are mentioned.